A case of IgE myeloma transformed into IgE-producing plasma cell leukaemia - Galakhoff, Nicolas (Array, 2020)
This is a case report of a challenging diagnosis of IgE monoclonal gammopathy of undetermined significance, which transformed into myeloma, then transformed into IgE-producing plasma cell leukaemia in a 71-year-old male who was followed in Brest, France, from 2015 to 2019. The IgEproducing variant is the rarest sub-type of multiple myeloma, and plasma cell leukaemia is considered to be the rarest and the most aggressive of human monoclonal gammopathies. In November 2015, hypogammaglobulinemia was detected during a systematic check-up. A kappa light chain monoclonal gammopathy was first diagnosed due to an increase of the free kappa/lambda light chains ratio. No monoclonal immunoglobulin was detected by either serum protein electrophoresis (Capillarys 2, Sebia, Issy-les-Moulineaux, France) or immunofixation (Hydrasys 2, Sebia, Issy-les-Moulineaux, France). In June 2018, a blood smear led to the diagnosis of plasma cell leukaemia. A monoclonal peak was detected and identified as IgE-kappa. Analysis of an archival sample taken three years earlier, revealed the presence of a monoclonal IgE, which had been missed at diagnosis. Chemotherapy with bortezomib and dexamethasone was introduced. The patient survived 10 months after the diagnosis of leukaemia. This case shows that an abnormal free light chain ratio should be considered as a possible marker of IgE monoclonal gammopathy even in the absence of a solitary light chain revealed by immunofixation. In addition, the use of an undiluted serum may increase the sensitivity of the immunofixation forthe detection of IgE monoclonal gammopathies compared to the 1:3 dilution recommended by the manufacturer.